Chemical Composition of Essential Oils from Flower and Leaf of Korean Mint, Agastache rugosa - Sung Lim, Soon; Man Jang, Jai; Tea Park, Woo; Romij Uddin, Md; Cheon Chae, Soo; Hoon Kim, Haeng; Un Park, Sang (Asian Journal of Chemistry, 2013)
This study aims at the qualitative and quantitative analysis of the essential oils extracted from the leaf and flower of Agastache rugosa. GC-MS analysis confirmed the presence of 43 compounds in the essential oils, 34 of which were common both in the leaf and in the flower. Seven compounds 2,6-dimethylheptane, 4-methyl-1-pentene-3-ol, d-limonene, trans-ocimene, octenyl acetate, anethole and 2-methyl-5-isopropenyl-2-cyclohexenone were present only in the flower, while b-damascenone and allyl-3-methyl-2-butanoate were present only in the leaf. The leaf and flower extracts of Agastache rugosa contained 36 and 41 compounds that constituted 90.93 and 82.3 % of the oils, respectively. Methylchavicol was the predominant component both in the leaf (84.25 %) and in the flower (57.94 %); the other major components in the flower were anethole, L-limonene and trans-caryophyllene, while those in the leaf were 2-phenyl propionaldehyde and trans-caryophyllene.